Management of chronic long standing condyle dislocation - Anehosur, Venkatesh; Mehra, Anhad; Kumar, Niranjan (International Surgery Journal, 2022)
Condyle dislocation accounts for 3% of all the dislocations of different joints in the body. They are basically classified based on duration as acute, chronic and recurrent, the most difficult to manage being chronic longstanding. This study of case series was carried out to enunciate and discuss optimal treatment protocols to enhance the postoperative result and functionally rehabilitate the patient. Data were recorded of patients of chronic long standing condyle dislocation (CLSCD) between 2012 to 2019. Predictor variables were drawn from demographics age, gender, aetiology, duration of dislocation status. The outcome variables were surgical success rate and complications. Surgical treatment included endaural pre auricular approach, high condylar shave with eminoplasty, elastic traction for a period of 5-7 days and mouth opening exercises. 15 patients with CLSCD of more than a month duration were identified out of 65 reported with other forms of acute and recurrent dislocation. The 12 (80%) were bilateral and 3 (20%) were unilateral. Three (20%) were of interpersonal violence, 3 (20%) had cerebrovascular accident, 3 (20%) following RTA with other major injuries, and 1 patient (6.6%) very rare unusual history of dislocation during labor pain reporting after six months. All patients had unsuccessful attempted conservative management. Surgical intervention and outcome were excellent. Complications recorded were 3 patients (20%) had transient facial nerve weakness, 2 (13.3%) infection. Conservative manipulation has definitive role in acute and recurrent cases but surgical approach or open procedure in chronic long-standing cases is the choice with duration of condylar dislocation being the decisive factor for difficulty index.